Debt Issuer: Credit Rating Agency Relations and the Trinity of Solicitude: An Empirical Study of the Role of Commitment - Duff, Angus (Journal of business ethics, 2015)
Interest in credit ratings agencies and their role in financial markets is at an all-time high. Concerns about a lack of transparency concerning process, conflicts of interest, and limited competition are frequently discussed by politicians, regulators and other commentators. These issues we term the credit ratings agency (CRA) trinity of solicitude. We shed some light on this trinity by considering the unique relationship that exists between corporate borrowers (debt issuers) and the CRAs they engage to rate their securities. The exchange relationships literature is used to create a model where commitment plays a central role. Technical qualities, relationship qualities and dependence are theorised as antecedents of commitment, which is described by two constructs of affective commitment and calculative commitment. The issuer’s intention to remain with the CRA, their loyalty, is the consequence of commitment. The model is operationalized by means of a survey questionnaire administered to issuers of corporate debt in the United Kingdom. As expected, perceptions of the quality of the relationship and affective commitment play an important role in CRA-issuer relations. However, contrary to expectations, the technical quality of the rating and issuer dependence on the CRA play little role in determining commitment and continuance. The implications of these findings are discussed along with areas for future research.